Designing a Risk Assessment Matrix for Algerian Port Operations - A BOUZAHER; L BAHMED; A BENOUDJIT (Journal of Failure Analysis and Prevention, 2015)
Port approach for merchant ships (regarding docking) is a special event related to the safety of ships and port facilities. This maneuvre is for emergency situations, and the consequences can be very damaging because there is a high risk of occurrence and severity can be high. In Algeria, 90% of foreign trade depends on shipping, and commercial vessels must dock in the port safely. This study aims to contribute to the management of risks associated with port operations by designing a matrix for specific assessment of this type of risk based on analysis of several incidents and accidents regarding maneuvring ships in Algerian ports. The design of the evaluation matrix of risks associated with port operations in Algeria is done in the context of the application of the Formal Safety Assessment methodology for improved performance of this method regarding precision and accuracy of results.